Effect of three intracanal medicaments used in pulp regeneration on the push-out bond strength of mineral trioxide aggregate and calcium-enriched mixture: An in vitro study - Negin Ghasemi; Hamidreza Yavari; Mohammad Samiei; Naser Asl Aminabadi; Fatemeh Dabbaghi Tabriz; Samra Taheri; Paria Davoudi (Tabriz University of Medical Sciences, 2022)
Background. The bond strength of the materials used as a cervical barrier in the pulp regeneration is essential for the success of treatment. This study aimed to evaluate the effects of triple antibiotic paste (TAP), double antibiotic paste (DAP), and simvastatin as intracanal medicaments on the dislodgement resistance of mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM). Methods. A total of 160 extracted human single-rooted teeth were selected, and root canal preparation was carried out. The teeth in each group were randomly divided into four subgroups: TAP, DAP, simvastatin, and the control group (without intracanal medicament). Four weeks after placing the medicaments, it was removed by sodium hypochlorite, and MTA and CEM were placed in the coronal third of the root canals. After a week, 2-mm-thick dentin disks were prepared from the coronal third of the roots, and the push-out test was performed using a universal testing machine. The data were analyzed using two-way ANOVA and independent t-test at a significance level of 0.05. Results. Regardless of the intracanal medicament, there was no significant difference between the overall bond strength of MTA (59.3±10 MPa) and CEM (55.8±11 MPa) (P=0.6). Furthermore, there were no significant differences in bond strength between the two intracanal medicament groups and the control group (P>0.05). Conclusion. Under the limitations of the current study, DAP, simvastatin, and TAP, as intracanal medicaments, did not adversely affect the push-out bond strength of CEM and MTA.